Realitätsnahe Bewertung des Einflusses der Oberflächenspannung flüssiger Zwischenmedien auf den maximalen Reibschluss zwischen Reifen und Fahrbahn - Bürckert, Matthias (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2019)
After a certain spell of dry weather, rain on the road can make the surface even more slippery. This is due mainly to surface contamination such as oil or dust, polluting the water and resulting in poor gripping of the road by the tires. In fact, as the contaminants substantially influence the viscosity and/or the surface tension, they also affect the surface-wetting property of the water; and this will eventually cause a severe decrease in the tire/road grip.